(untitled) (Canadian Eye Care Today, 2022)
Dupilumab is an immunomodulatory medication blocking interleukins. This biologic drug is an injectable human monoclonal antibody targeting the α subunit of interleukin (IL)-4 which affects the IL-4 and IL-13 pathways. Since its approval by the United States Food and Drug Administration and Health Canada in 2017, it has been used extensively for the treatment of multiple diseases, including chronic rhinosinusitis with nasal polyposis, asthma, and most notably atopic dermatitis. In patients with moderate-to-severe atopic dermatitis (AD), dupilumab has significantly improved patients’ quality of life. In the pivotal SOLO 1 and SOLO 2 trials involving patients aged 18 years and older, dupilumab was compared with placebo and demonstrated a significant reduction in Investigator Global Assessment (IGA) atopic dermatitis score down to “clear” or “almost clear” (i.e., 0 or 1) and a ≥ 2-point improvement from baseline in that same score at week 16. This primary endpoint was achieved in 36-38% of patients on dupilumab compared with 8–10% of patients on placebo. However, these outcomes are not without drawbacks. The emergence of dupilumab-associated ocular surface disease (DAOSD) or dupilumab-induced ocular surface disease (DIOSD) is now commonly reported by both dermatologists and ophthalmologists who treat AD patients using dupilumab. Interestingly, dupilumab has not been associated with increased conjunctivitis rates in studies in other diseases, including asthma and chronic rhinosinusitis with nasal polyposis, which suggests that the increased rates of conjunctivitis in AD studies may reflect a unique interaction between AD and dupilumab-related mechanisms. The SOLO 1 and SOLO 2 trials were the first to detect a higher rate of conjunctivitis in dupilumab-treated patients with 3-5% of the dupilumab-treated patients developing “conjunctivitis of an unspecified cause” compared to 1% in the placebo groups, with 1 of 920 patients discontinuing dupilumab because of conjunctivitis in SOLO 1. The highest rate among dupilumab trials was in LIBERTY AD CAFÉ where conjunctivitis was reported in 16%, 28% and 11% of patients in the weekly dupilumab + topical corticosteroid (TCS), every two weeks + TCS and placebo + TCS groups, respectively; all but one event were mild or moderate. However, in those trials patients did not undergo complete ophthalmological examinations to characterize the type of ocular involvement that was reported. Subsequent research and real-world experience has since detailed the variety of findings associated with DAOSD. With more studies now published, including those which involve subjects examined by ophthalmologists, we have a better idea of the incidence of DAOSD. A recent Canadian study reported a rate of DIOSD at 37% over a 52-week follow-up period, with 19% of these patients requiring a consultation in ophthalmology. Most of the time, only the most severe cases will be referred to ophthalmologists, while milder cases will be treated by dermatologists or primary care providers through the use of artificial tears. The aim of this article is to provide a basic framework for clinicians to understand the pathophysiology of DAOSD, how to diagnose DAOSD, and the optimal treatment strategy for these patients.